2006
DOI: 10.1111/j.1365-2648.2006.03802.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of childhood fever by parents: literature review

Abstract: Despite successful educational interventions, little has changed in parents' fever management knowledge, attitudes and practices. There is a need for interventions based on behaviour change theories to target the precursors of behaviour, namely knowledge, attitudes, normative influences and parents' perceptions of control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
105
1
34

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(147 citation statements)
references
References 55 publications
7
105
1
34
Order By: Relevance
“…This result is supported by previous research, which stated that the knowledge of parents about normal body temperature in children, the function of fever and its handling is still low. 16,17 . On the research of Abu Baker et al some parents even have a less adequate knowledge about the fever management, of which more than half the mothers do not understand that lowering the room temperature can lower the children's body temperature and most of the mothers do not recognize that the seizures are the most common effects on child's fever.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is supported by previous research, which stated that the knowledge of parents about normal body temperature in children, the function of fever and its handling is still low. 16,17 . On the research of Abu Baker et al some parents even have a less adequate knowledge about the fever management, of which more than half the mothers do not understand that lowering the room temperature can lower the children's body temperature and most of the mothers do not recognize that the seizures are the most common effects on child's fever.…”
Section: Discussionmentioning
confidence: 99%
“…The use of antipyretic and give compress was done by parents to lower a fever because of their worry about the harmful effects of fever. 15,16,18 The parents provide a medicine at a time when body temperature below 38 °C due to worry about the side effects of fever such as brain damage, chronic disease, blindness, and coma. Giving antipyretic drug that is less precise, can lead to overdose and ineffectiveness of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…9 These misconceptions will often lead to the mismanagement and inappropriate treatment of fever, such as the use of inappropriate medicines, frequent temperature readings and overuse of healthcare services. 10 An example of this includes the routine use of antipyretics given to febrile children even though there is no evidence to suggest they reduce the morbidity of fever. 11 Antipyretics such as acetaminophen (paracetamol) are able to moderately lower the core body temperature by approximately 1-2°C and may provide some analgesic relief, 12 although strong evidence for this is still lacking.…”
Section: R a F T A J P E A C C E P T E D D R A F Tmentioning
confidence: 99%
“…Randomized controlled trials of parent educational programs in clinics and EDs have shown that they can be effective in decreasing calls to paediatricians and ED visits (30). Thus, while our understanding of the determinants of fever phobia is incomplete, clinicians appear to be well placed to educate parents on how to deal with this common symptom.…”
Section: Discussionmentioning
confidence: 99%